Hydrogen Treatment for Superparamagnetic VO2 Nanowires with Large Room‐Temperature Magnetoresistance. (6th June 2016) - Li, Zejun; Guo, Yuqiao; Hu, Zhenpeng; Su, Jihu; Zhao, Jiyin; Wu, Junchi; Wu, Jiajing; Zhao, Yingcheng; Wu, Changzheng; Xie, Yi
Abstract: One‐dimensional (1D) transition metal oxide (TMO) nanostructures are actively pursued in spintronic devices owing to their nontrivial d electron magnetism and confined electron transport pathways. However, for TMOs, the realization of 1D structures with long‐range magnetic order to achieve a sensitive magnetoelectric response near room temperature has been a longstanding challenge. Herein, we exploit a chemical hydric effect to regulate the spin structure of 1D V–V atomic chains in monoclinic VO2 nanowires. Hydrogen treatment introduced V 3+ (3d 2 ) ions into the 1D zigzag V–V chains, triggering the formation of ferromagnetically coupled V 3+ –V 4+ dimers to produce 1D superparamagnetic chains and achieve large room‐temperature negative magnetoresistance (−23.9 %, 300 K, 0.5 T). This approach offers new opportunities to regulate the spin structure of 1D nanostructures to control the intrinsic magnetoelectric properties of spintronic materials.